A Systematic Review of Qualitative Studies Investigating Motives and Experiences of Recipients of Anonymous Gamete Donation - Bauer, Tobias (Frontiers in Sociology, 2022)
The decision to use an anonymous gamete donation in fertility treatment could have significant long-term psychological and social effects for all stakeholders involved. In light of the growing recognition of donor-conceived children’s right to know their genetic parentage, this entails profound ethical implications. This review aims to carve out the full spectrum of recipients’ motives and experiences related to donor anonymity which could serve as an analytical framework for future ethical and sociological research on issues of donor anonymity. This review was conducted following a seven-step approach for systematic reviews of empirical bioethics literature. The characteristics and quality of the studies included in this review were reported. Data analysis was conducted using qualitative content analysis and was informed by sociological functionalist theorizations of ignorance. The 53 studies selected showed a diverse spectrum of characteristics concerning date and country of study, methodology, family type of participants, sample size, and the timing of data collection in relation to the stage of treatment. A total of 22 categories of motives and experiences of recipients concerning donor anonymity were identified inductively and grouped into five main categories. Donor anonymity was identified as a eufunctional form of ignorance, by which the recipients experienced or intended to control, regulate, or protect inter-stakeholder relations. Interpreting recipients’ motives and experiences concerning donor anonymity as a form of ignorance directed toward particular stakeholders helps reframe the discourse on donor anonymity. It is a fruitful approach that can be refined further and applied in future research. This review identified possible directions for future investigations on motives for donor anonymity: the need for more thorough inquiries into the change in recipients’ preferences over time, such as in the form of longitudinal studies and research on the perspective of non-biological parents.